PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA DAN DAMPAKNYA PADA KINERJA PEGAWAI DINAS PEMUDA DAN OLAHRAGA PROVINSI SUMATERA SELATAN - Irwanto, Irwanto; Hendro, Omar; Adjeng Moelyati, Trisniarty (Universitas Muhammadiyah Palembang, 2021)
Purpose – The Influence Of Discipline and The Work Environment On Work Motivation and Its Impact On Employee Performance For Employees Of Youth and Sports In South Sumatera ProvinceDesign/methodology – The infrential analysis used in this study is the path analysis approach. The path analysis model is used to analyze the pattern of relationships between variables in order to determine the direct or indirect effect of a set of independent (exogenous) variables on the dependent (endogenous) variable. Findings - The results of this study conclude 1). There is a significant influence between Work Discipline on Work Motivation. 2). There is a significant influence between the Work Environment on Work Motivation. 3). There is a significant influence between Work Discipline on Employee Performance. 4). There is a significant influence between the Work Environment on Employee Performance. 5). There is a significant influence between Work Motivation on Employee Performance in the Employees of the Youth and Sports Office of South Sumatra Province.